Impaired Spontaneous Baroreceptor Reflex Sensitivity in Patients With COPD Compared to Healthy Controls: The Role of Lung Hyperinflation - Mayr, Anna Katharina; Wieser, Victoria; Funk, Georg-Christian; Asadi, Sherwin; Sperk, Irene; Urban, Matthias Helmut; Valipour, Arschang (Frontiers in Medicine, 2022)
BACKGROUND AND OBJECTIVES Patients with chronic obstructive pulmonary disease (COPD) are at increased risk for cardiovascular disease. This study aimed to investigate the relationship between pulmonary hyperinflation and baroreceptor reflex sensitivity (BRS), a surrogate for cardiovascular risk. METHODS 33 patients with COPD, free from clinical cardiovascular disease, and 12 healthy controls were studied. Participants underwent pulmonary function and non-invasive hemodynamic measurements. BRS was evaluated using the sequence method during resting conditions and mental arithmetic stress testing. RESULTS Patients with COPD had evidence of airflow obstruction (forced expiratory volume in one second predicted (FEV1%) 26.5 [23.3 to 29.1] vs. 91.5 [82.8 to 100.8]; P<0.001; geometric means [GM] with 95% confidence interval [CI]) and lung hyperinflation (residual volume/total lung capacity [RV/TLC] 67.7 [64.3 to 71.3] vs. 41.0 [38.8 to 44.3]; P<0.001; GM with 95% CI) compared to controls. Spontaneous mean BRS (BRSmean) was significantly lower in COPD, both during rest (5.6 [4.2 to 6.9] vs. 12.0 [9.1 to 17.6]; P=0.003; GM with 95% CI) and stress testing (4.4 [3.7 to 5.3] vs. 9.6 [7.7 to 12.2]; P<0.001; GM with 95% CI). Stroke volume (SV) was significantly lower in the patient group (-21.0 ml [-29.4 to -12.6]; P<0.001; difference of the means with 95% CI). RV/TLC was found to be a predictor of BRS and SV (P<0.05 for both), independent of resting heart rate. CONCLUSION We herewith provide evidence of impaired BRS in patients with COPD. Hyperinflation may influence BRS through alteration of mechanosensitive vagal nerve activity.